Relación entre la recaudación tributaria y el control interno en la Municipalidad de Mazán durante el periodo 2022 - Morey Flores, Diego Rodrigo (2025)
This research examines the relationship between internal control and tax collection in the Municipality of Mazán during the year 2022. Using a quantitative and correlational approach with a non-experimental design, the perceptions of 97 municipal workers were evaluated through surveys. The results confirm the general hypothesis that there is a positive relationship between internal control and tax collection, with a Spearman correlation coefficient of 0.2541 and a p-value of 0.0462. Furthermore, two specific hypotheses were validated: a strong positive relationship between collection efficiency and the control environment (ρ = 0.7823, p = 0.003), and another between the amount of taxes collected and risk assessment (ρ = 0.7947, p = 0.002). These correlations suggest that improvements in internal controls and risk management are crucial to optimize collection. Based on these findings, measures such as the creation of an internal control committee, training programs for staff, and the implementation of a tax risk management system are recommended. These actions seek to strengthen fiscal efficiency and ensure sustainable, transparent and effective tax collection in the municipality.